Keragaan Dan Daya Hasil Beberapa Varietas Jagung Lokal Pulau Kisar, Kabupaten Maluku Barat Daya - Akerina, Allinsia Meilany; Laisina, Jane K J; Raharjo, Simon H T (Universitas Pattimura, 2024)
This research aimed to determine the performance and yield of several local corn acccessions from Kisar Island, Maluku Barat Daya (MBD) or Southwestern Maluku Regency. This research was carried out on the field of the Kisar Island Agricultural Extension Center located in Lebelau Village, MBD Regency from November 2022 to February 2023. The research was carried out as an experiment designed as a single factor Randomized Block Design, with 4 replicates. The single factor was corn accession/variety consisting of four local corn accessions from Kisar Island and one superior variety of Sukmaraga as a comparison. The results of this study showed that local corn from Kisar Island in the form of the Merah Delima Kisar accession had the highest values for the variables of plant height, leaf number, and cob height when compared with the Putih Kisar accession, the Kuning Bunga Kisar accession and the Ungu Kisar accession. The Putih Kisar accession had high values for cob plus kernel weight with husks (145.40 g), cob plus kernel weight without husks (127.33 g), fruit diameter (4.08 cm), cob length (13.98 cm), number of kernels per plant (391.75), weight of 100 kernels (33.00 g) and kernel weight per plant (114.09 g), when compared with the Merah Delima Kisar, Kuning Bunga Kisar, and Ungu Kisar accessions. The Putih Kisar and Merah Delima Kisar accessions showed high yields. They were not significantly different from the Sukmaraga variety, which had the highest yields based on kernel weight per plant.